THE NATURE OF RIGHTS AND ACCESS TO THE INTERNET - Eloff, Daniel (Obiter, 2023)
The question of whether a right to Internet access exists often centres around whether it “should” be a right and not whether it “could” be a right. Although some proponents of Internet-access-as-a-right might hold lofty and praiseworthy ideals, something does not become a right simply by being proclaimed as a right. That would be a superficial and hollow perception of the nature of rights. The admirable desire to grant a “rights” status to access to the Internet is as seductive as it is problematic. The Internet is a medium that enables the exercise of other rights but access to the Internet is not a right in itself. Moreover, the Internet as a medium is not intrinsic to being human. To proclaim access to the Internet as a right therefore unthoughtfully diminishes the very nature of rights. The proposition is perilous, given the context of South Africa’s struggle to ensure rights for all who live here, and it cheapens those rights that have been won.